A new carbohydrate retaining variety of Miscanthus increases biogas methane yields compared to M x giganteus and narrows the yield advantage of maize. (6th July 2020) - Kam, Jason; Thomas, David; Pierre, Sandra; Ashman, Chris; McCalmont, Jon P.; Purdy, Sarah J.
Abstract: Anaerobic digestion (AD) currently relies heavily on crop feedstocks to maintain a constant output. A major annual crop used is Zea mays (maize), but this practice presents significant concerns because high energy inputs and food‐growing land are required for cultivation. The autumn harvest date of maize exposes soils over winter resulting in erosion and runoff into waterways. Miscanthus is physiologically and morphologically similar to maize. It is also of interest for biogas generation. As a perennial grass, Miscanthus requires far less input and can be grown on land that is unsuitable for food crops. It is typically harvested in late winter to early spring. Maize produces higher biogas yields than the most commonly grown commercial variety of Miscanthus (Mxg), because it has a higher nonstructural carbohydrate (NSC) concentration that facilitates the AD process. We aimed to investigate whether a new Miscanthus hybrid ("GNT‐14") that was bred from a high carbohydrate accumulating parental type can improve biogas yield from Mxg. Comparisons were made on biogas yields at two time points, October and January; the NSC, cellulose, and lignin concentrations were quantified; and the contribution of the NSC to biogas yield was determined by comparing intact and washed samples. The NSC concentrations of GNT‐14 were fivefold higher than Mxg in January, and a 28% increase in methane was observed. While Mxg showed a reduction in methane yields (L/kg) from biomass harvested in January compared to October, GNT‐14 showed no such decline. Although the potential methane yields of GNT‐14 were only 70% that of maize, the energy input (GJ ha ‐1 ) required for cultivation was 26% of maize. Our results demonstrated that GNT‐14 could be harvested later than maize for biogas generation, offering soil protection over winter. We encourage Miscanthus breeding efforts to focus on NSC concentration as well as yield. Abstract : Anaerobic digestion currently relies heavily on crop feedstocks to maintain a constant output. A major annual crop used is Zea mays (maize), but this practice presents significant concerns because high energy inputs and food‐growing land are required for cultivation. The autumn harvest date of maize exposes soils over winter resulting in erosion and runoff into waterways. Our results demonstrate that GNT‐14 could be harvested later than maize, offering soil protection over winter.